Spatial distribution of aquatic Oligochaeta in Ilha Grande National Park, Brazil - doi: 10.4025/actascibiolsci.v35i1.10768 - Ragonha, Flávio Henrique; Chiaramonte, Josiane Barros; Fontes Junior, Hélio Martins; Cunha, Eduardo Ribeiro da; Benedito, Evanilde; Takeda, Alice Michiyo (Acta Scientiarum. Biological Sciences, 2012)
Ilha Grande National Park is an important conservation unit localized in the Southern part of the upper Paraná river floodplain (Brazil) that includes diverse aquatic environments. Oligochaeta (Annelida) is a large group of invertebrates, with several small specimens inhabiting almost every possible niche at most freshwater ecosystem. The goal of the present study was to examine the spatial variation of Oligochaeta community in five floodplain lakes from the Ilha Grande National Park and relate the distribution with abiotic variables. Samples were taken at five sampling stations using a modified Petersen grab. Thirteen species of Oligochaeta belonging to two families Naididae and Tubificidae were recorded. Different patterns of richness and abiotic factors were identified among the lakes located in the island and at the margin of Paraná river. The different patterns of granulometric texture affected directly the distribution of the Oligochaeta assemblage of theses environments. The results of this study permit to infer that the Oligochaeta assemblage, in preserved areas, present a higher richness in relation to long term studies with more frequent samplings. We concluded that Ilha Grande National Park contributes for the preservation of benthic invertebrates.